PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI KONVEKSI WD WILLD OUTDOOR PAGERAGEUNG - Mahmudah, Ai Rifaatul; Yayan Rudianto; Bambang Kurnia Nugraha; Erna Rusmiwati Sukandar (Journal of Innovation Research and Knowledge, 2025)
The problem in this research is related to employee productivity at WD Willd Outdoor Convection, which influenced by the work environment and work discipline. The study aims to: 1) determine the condition of the work environment at WD Willd Outdoor Convection 2) determine the level of work discipline at WD Willd Outdoor Convection 3) determine employee productivity at WD Willd Outdoor Convection, and 4) determine the effect of the work environment and work discipline to employee productivity at WD Willd Outdoor Convection. The method used in this research is descriptive with a replicative nature. This study uses primary data collected through the distribution of questionnaires measured by using a likert scale. The sample in this study amounted to fifty five respondents. The analytical tool used, is multiple linear regression analysis. The results of this study indicate that: 1) the work environment at WD Willd Outddor Convection is considered goog 2) the level of Work discipline is considered good 3) employee productivity is also considered good, and 4) Based on the results of multiple linear regression analysis, the influence of the work environment and work discipline to employee productivity is positive and has a significant effect.